In vivo oral breakdown properties of whey protein gels containing OSA-modified-starch-stabilized emulsions: Impact of gel structure. (April 2021) - Lin, Quanquan; Liang, Rong; Zhong, Fang; Ye, Aiqian; Singh, Harjinder
Abstract: This study investigated the effects of gel structure on the in vivo oral breakdown properties of whey protein gels containing emulsion droplets stabilized by octenyl succinic anhydride (OSA)-modified starches. The gel structure was manipulated by the degree of substitution (DS) of the OSA-modified starch and the salt concentration. Rheological measurements showed that, when the DS or the NaCl concentration increased, the storage modulus, hardness and Young's modulus of the gels increased. Hard gels (100 mM NaCl) required more chewing cycles than soft gels (10 mM NaCl), which led to smaller mean particle size ( d 50 ) of the bolus. Correlation analysis showed that d 50 had an excellent power-law relationship with hardness and Young's modulus, whereas it had a positive linear relationship with fracture force and fracture strain. This indicated that the physical/mechanical properties of the gel were the critical factors that determined the bolus particle size. During oral processing, there were no significant changes in the microstructures of the gels and only very few oil droplets were released from the protein matrix, suggesting that the OSA-modified-starch-stabilized emulsion droplets remained bound within the whey protein gel matrix. Graphical abstract: Image 1 Highlights: Higher DS of OSA-modified starches led to greater gel strength of emulsion gels. Hard gels required more chewing cycles than soft gels. d 50 of bolus had power-law relationship with hardness and Young's modulus of gel. d 50 had positive linear correlation with fracture force and fracture strain of gel.